The Psychometric Properties of the Norwegian version of The Social Phobia and Anxiety Inventory for Children (SPAI-C) - Aune, Tore; Hjemdal, Odin (PsykTestBarn, 2017)
Description: SPAI-C is developed by S.M. Turner, D.S. Beidel, and T.L. Morris and was firstly reported and described internationally in 1995, and in Norway in 2008. The instrument was translated to Norwegian by Tore Aune, Kyrre Svarva and Hanne Kristiansen. The back-translation was undertaken by the psychologists Jeanette Hawkins and Torill Ueland. SPAI-C consist of 26 items. Each item is rated on a three point Likert scale. In Norway SPAI-C has been used in a clinical context, as a screening instrument in population studies, as well as an outcome measure in clinical studies. Regarding scoring 18 points have been recommended as the clinical cut-off score. The instrument is primarily developed for children and adolescents in the age 8-14 years. A third grade reading level is normally needed for SPAI-C. Normally it will take between 10-20 minutes to fill out the scale. To administer and interpret SPAI-C it is recommended a competency of level B (Master levels) in accordance with Multi-Health Systems inc. qualification demands. SPAI-C is copyright protected and in order for access to the instrument, contact the copyright owner. Literature search: The search for documentation of the measurement qualities of SPAI-C resulted in 22 original references, of which nine were included. Six Norwegians and three Swedish. Three of the included studies were cross-sectional, four were intervention studies, while two studies had a longitudinal design. SPAI-C has been used in clinical, normal and population samples. For the nine included studies, the samples consisted of boys and girls between 11 and 15 year. Psychometrics: All nine studies reported mean scores, some for boys and girls separately. Two studies explored the factors structure of SPAI-C, while five studies reported construct validity, and in two studies reported test-retest, concurrent and discriminate validity. The psychometric properties of SPAI-C were evaluated to be good. Reported reliability scores were above 0.90 across studies. Expected associations with depression, several anxiety disorders, clinical observations and interviews supported the validity of SPAI-C. SPAI-C seems sensitive to identify adolescents that satisfy the criterion of social anxiety disorder, but tend to identify too many false positives. Further, the SPAI-C is sensitive to change over time, among adolescents that attend therapy. In population studies, a five-factor solution was found, while clinical studies support a three-factor solution. Conclusion: Scandinavian studies indicate that the measurement quality of SPAI-C are adequate, and that it is a useful self-report scale for identifying adolescents with social anxiety symptoms.